Suitability Index and Supporting Capacity of Mangrove Ecotourism in Darunu Mangrove Park Wori District North Minahasa Regency - Gultom, Fernando; Paruntu, Carolus Paulus; Rumengan, Antonius Petrus; Rumampuk, Natalie D. C.; Paransa, Darus S. J.; Ompi, Medy (Sam Ratulangi University, 2024)
The purpose of the study was to determine the type of mangrove, mangrove density, mangrove thickness, tides, associated biota objects, tourism suitability index, and carrying capacity of the Darunu mangrove tourism area. The research period is October-December 2023. The research methods used are cruising survey for mangrove species, line transect for mangrove density, remote sensing for mangrove thickness, and visualization for associated biota objects. Data analysis for the tourism suitability index (IKW) and area carrying capacity (DDK) is guided by the provisions of Yulianda (2019). The IKW value is 2.0 with the appropriate category and the DDK value is 25 people per day. The size of the DDK value of the mangrove tourism area depends on two main factors, namely the length of tracking and the length of operating time. The greater the value of tracking length and the length of operating time, the greater the DDK value, conversely the smaller the value of tracking length and the length of operating time, the smaller the DDK value. As a recommendation to the village government to be able to extend the tracking distance by utilizing the mangrove spaces that are still available, in addition to the tourist period can be extended with adequate facilities such as electricity, lighting, etc. so that the value of DDK can still be achieved as much as possible to increase the economic income of the village community while still paying attention to environmental sustainability. Furthermore, community participation to preserve this mangrove forest area is needed for the sustainability of ecotourism-based mangrove tourism at Darunu Mangrove Park. Keywords: Area carrying capacity, Darunu Mangrove Park, Ecotourism, Mangrove, Tourism suitability index. Abstrak Tujuan penelitian adalah untuk mengetahui jenis mangrove, kerapatan mangrove, ketebalan mangrove, pasang surut air laut, objek biota asosiasi, indeks kesesuaian wisata dan daya dukung kawasan wisata Darunu Mangrove Park. Periode penelitian yaitu Oktober-Desember 2023. Metode penelitian yang digunakan yaitu survey jelajah untuk jenis mangrove, transek garis untuk kerapatan mangrove, penginderaan jauh untuk ketebalan mangrove, visualisasi untuk objek biota asosiasi. Analisis data untuk indeks kesesuaian wisata (IKW) dan daya dukung kawasan (DDK) berpedoman pada ketentuan dari Yulianda (2019). Nilai IKW sebesar 2,0 dengan kategori sesuai dan nilai DDK sebanyak 25 orang per hari. Besar kecilnya nilai DDK kawasan wisata mangrove tergantung pada dua faktor utama, yaitu panjang tracking dan lamanya waktu operasi. Semakin besar nilai panjang tracking dan lamanya waktu operasi, maka semakin besar pula nilai DDK tersebut, sebaliknya semakin kecil nilai panjang tracking dan lamanya waktu operasi maka semakin kecil nilai DDK tersebut. Sebagai rekomendasi kepada pemerintah desa untuk dapat memperpanjang jarak tracking dengan memanfaatkan ruang-ruang mangrove yang masih tersedia, disamping itu periode waktu wisata dapat diperpanjang dengan dilengkapi fasilitas yang memadai seperti listrik, penerangan, dan lain-lain, agar nilai DDK masih dapat dicapai semaksimal mungkin dalam rangka peningkatan pendapatan ekonomi masyarakat desa dengan tetap memperhatikan kelestarian lingkungannya. Selanjutnya peran serta masyarakat untuk menjaga kelestarian kawasan hutan mangrove ini sangat dibutuhkan demi keberlanjutan wisata mangrove berbasis ekowisata di Darunu Mangrove Park. Kata kunci: Daya dukung kawasan, Darunu Mangrove Park, Ekowisata, Indeks kesesuaian wisata, Mangrove.